(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
Ten years after the fall of Gaddafi’s regime, Libya still has not adopted a permanent constitution. Over the last decade, both national bodies and transnational actors have taken part in constitution-making; however, all efforts have been unsuccessful so far. While the scholarship on post-2011 Libya has mainly focused on the impact of local events and national actors on this process, this essay outlines the recent history of Libya’s constitution-making by stressing the intermingling of the activities of local bodies and transnational actors. By using the theorical lens of transnational legal orders (TLOs), it claims that two TLOs – the Western liberal democratic TLO and the Islamic one - will coexist if the 2017 draft constitution is adopted. Nevertheless, both TLOs would be necessary to reinforce the legitimacy of the constitution before, on the one hand, international organisations and Western countries and the Libyan population, on the other.